APPLIED BEHAVIOR ANALYSIS IN ACQUIRED BRAIN INJURY REHABILITATION: A META‐ANALYSIS OF SINGLE‐CASE DESIGN INTERVENTION RESEARCH - Heinicke, Megan R.; Carr, James E. (Behavioral interventions, 2014)
The purpose of this meta‐analysis was to complete a systematic evidence‐based review of published behavioral treatment studies employing single‐case designs with both children and adults with acquired brain injury. Peer‐reviewed journals were searched using PsycINFO, Medline, and ERIC databases with combinations of terms such as brain injury, behavior disorder, behavior therapy, behavior modification, behavior analysis, and verbal behavior. A total of 112 acquisition and reduction studies met the established inclusion criteria. The data extracted from each study included specific details about the participants, target responses, intervention characteristics, use of functional assessment, and outcome characteristics. A data extraction software program was also used to extract data from graphs to calculate percentage of nonoverlapping data as an effect size. The studies were then evaluated along several dimensions from multiple evidence‐based practice frameworks. Collectively, interventions targeted a wide range of behaviors for acquisition and reduction, but only five interventions were classified as well established according to the American Psychological Association Division 12 criteria. Furthermore, methodology of the identified studies was found to be relatively poor. A variety of methodological concerns are discussed. Copyright © 2014 John Wiley & Sons, Ltd.